DOI: 10.11606/t.59.2014.tde-18122014-143500
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia encefálica comparada de Characiformes (Teleostei: Ostariophysi)

Abstract: Acestrorhynchidae como clado-irmão de Erythrinoidea; Gasteropelecidae + Triportheidae + Bryconidae sendo mais relacionados entre si; Crenuchidae como grupo-irmão de Characidae. Além dessas relações, corroborramos a elevação de algumas subfamílias de Characidae para o status de família, como Acestrorhynchidae, Bryconidae, Cynodontidae, Iguanodectidae e Triportheidae. A família Characidae tendo Heterocharacinae como ramo basal e sustentada principalmente por caracteres osteológicos tendo adicionalmente, um carát… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…1). The anatomical brain nomenclature follows Meek & Nieuwenhuys (1998) and Striedter (2005); bone nomenclature follows Weitzman (1962), with the modifications proposed by Castro & Vari (2004) and musculature terminology follows Datovo & Vari (2013;2014). (Figs.…”
Section: Brain Dissection Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The anatomical brain nomenclature follows Meek & Nieuwenhuys (1998) and Striedter (2005); bone nomenclature follows Weitzman (1962), with the modifications proposed by Castro & Vari (2004) and musculature terminology follows Datovo & Vari (2013;2014). (Figs.…”
Section: Brain Dissection Protocolmentioning
confidence: 99%
“…Among the Otophysi (composed by the Orders Cypriniformes, Characiformes, Siluriformes and Gymnotiformes), the study of the brain gross morphology has recently been addressed for gymnotiforms (Albert et al, 1998;Albert, 2001), in addition to the siluriforms Callichthyidae and Pseudopimelodidae (Abrahão & Shibatta, 2015), the Callichthyidae which was the subject of a Master's dissertation (Pupo, 2011) and the Characiformes studied in a Doctoral thesis (Pereira, 2014), both unpublished at this moment. These Otophysi brain studies have unequivocally shown that the central nervous system can be an important source of phylogenetically informative morphological characters, although relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…This results in some divergent morphological patterns found among phylogenetic distant taxa (Kotrschal & Palzenberger, 1992;Eastman & Lannoo, 1995;van Staaden et al, 1995;Ito et al, 2007). However, some recent works on neotropical fish brains in a systematic framework show evidences that several sub-units have their shape due to shared evolutionary history rather than ecology (Gonzalez-Voyer & Kolm, 2010;Pupo, 2011;Abrahão, 2013;Pereira, 2014;Pupo, 2015;Abrahão et al, 2018).…”
Section: Introductionmentioning
confidence: 99%